Aspects of structural degradation in old bridge steels by means of fatigue crack propagation - Lesiuk, G.; Szata, M. (Фізико-хімічна механіка матеріалів, 2011)
The paper presents conclusions drawn from studies related to old steel structures, especially those erected on the turn of the 19th century. The objects of interest of the authors were Wroclaw Pomorskie Bridges: the Central Pomorski Bridge and the North Pomorski Bridge (1885, 1930 respectively), as well as the Sand Bridge (1861). The material used for their construction was puddled steel or cast steel. In the course of long operation the steels (especially the puddled one) show susceptibility to degradation processes. In this paper the results of metallographic tests (light microscopy, SEM) and mechanical properties tests (hardness measurement, static tensile test) presenting the state of structural degradation have been presented. Also, the initial study results for the puddled steel coming from the Sand Bridge and concerning development of a fatigue crack have been presented. Basic quantities describing the kinetics of fatigue crack growth have been determined. Досліджено сталі мостів біля Вроцлава (Польща): дві пудлингові, експлуатовані з 1861 і 1885 рр., а також ливарну (1930 р.). Сталі, особливо пудлингові, чутливі до деградаційних процесів, що проявилось у зміні структури і механічних властивостей, найвідчутніше – у зниженні опору втомному росту тріщини. Исследованы стали мостов в районе Вроцлава (Польша): две пудлинговые, эксплуатируемые с 1861 и 1885 гг., а также литейную (1930 г.). Стали, особенно пудлинговые, чувствительны к деградационным процессам, что проявилось как в изменении структуры, так и механических свойств, наиболее значительно – в понижении сопротивления усталостному росту трещин.